The effect of improving the quality of products in livestock breeding by innovative methods - Bahodirjon Nosirov; Elyorbek Nurmatov (Zien Journals, 2023)
The article looks at creative methods to raise product quality and increase agricultural productivity in the cattle industry. Simultaneously, the efficiency indicators for raising animal breeds and raising feed quality in order to produce high-fat milk were examined. Modern assessment techniques and quality performance requirements must be thoroughly understood while creating, delivering, and planning highquality goods.
Keywords: animal husbandry; cattle breeding; intensive method